2016
DOI: 10.1002/jcp.25685
|View full text |Cite
|
Sign up to set email alerts
|

A Real‐World Multicentre Retrospective Study of Paclitaxel‐Bevacizumab and Maintenance Therapy as First‐Line for HER2‐Negative Metastatic Breast Cancer

Abstract: Bevacizumab in combination with taxanes in HER2‐negative metastatic breast cancer (MBC) patients has shown improved progression‐free survival (PFS), despite the lack of clear overall survival (OS) benefit. We performed a retrospective analysis to evaluate the impact of paclitaxel‐bevacizumab and of maintenance therapy with bevacizumab (BM) and endocrine therapy (ET) in the real‐world practice. We identified 314 HER2‐negative MBC patients treated in 12 cancer centers. Overall, the median PFS and OS were 14 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 36 publications
(54 reference statements)
1
29
1
1
Order By: Relevance
“… 32 Furthermore, several real-world studies have shown that MHT in combination with maintenance bevacizumab is associated with either improved PFS, 33 or improved PFS and OS. 27 , 31 These findings, in conjunction with the findings of the present study, suggest that the addition of hormonal therapy to maintenance bevacizumab after first-line bevacizumab-based therapy is a promising treatment option for patients with hormone receptor-positive MBC.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“… 32 Furthermore, several real-world studies have shown that MHT in combination with maintenance bevacizumab is associated with either improved PFS, 33 or improved PFS and OS. 27 , 31 These findings, in conjunction with the findings of the present study, suggest that the addition of hormonal therapy to maintenance bevacizumab after first-line bevacizumab-based therapy is a promising treatment option for patients with hormone receptor-positive MBC.…”
Section: Discussionsupporting
confidence: 77%
“… 23 In real-world studies, the median PFS and OS ranged from 8 to 14 months and from 21 to 40 months, respectively. 19 , 24 27 Furthermore, the ORR was also higher in the present study than in other real-world studies (60%–70%), 26 , 27 as well as in the long-term treatment subgroup in the ATHENA study (68%). 23 …”
Section: Discussioncontrasting
confidence: 49%
“…This patient subgroup originated from a larger cohort, whose treatment outcomes had been addressed in previous work. 7 In the present manuscript, data where analyzed to assess the impact of BMI on treatment outcomes. In the overall patient cohort, stratification by BMI did not affect ORR or DCR, neither did we observe any effect in the luminal type subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…The methods applied were extensively reported elsewhere. 7 Briefly, in the main study, HER2-negative MBC patients were identified and recruited from 12 Italian cancer centres. Treatment administration was compliant with the most updated indications and recommendations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation